The Tradition of Return : The Implicit History of Modern Literature - Perl, Jeffrey M. (Book collections on Project MUSE., 2014)
Jeffrey Perl presents in this book a comprehensive reassessment of modernism and an effort to enrich our understanding of the direction literary culture has taken since the Renaissance. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library i.